Electrochemical device and positive electrode active material

CN122950562APending Publication Date: 2026-10-20BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511179194.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-21
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

但随着三元正极活性材料的加入,当三元材料的掺混量较少时,会导致三元材料的容量发挥不完全,当三元材料的掺混量较多时,会导致电化学装置的循环寿命衰减加速

Benefits of technology

[0022]本申请中,将I×P×D×k的数值范围限定在0.2到5.7之间,以此确保电化学装置同时具备较高的能量密度和优异的循环性能。具体来说,参数I表示正极活性材料中锂过渡金属氧化物的占比,参数P表示正极活性材料的压实密度,参数D表示正极活性材料的体积平均粒径Dv50,参数k表示锂过渡金属氧化物的晶体类型(区分单晶与多晶),这四个参数的数值与电化学装置的性能呈现出负相关关系:参数数值越高,电化学装置的能量密度越能得到提升,而参数数值越低,电化学装置的循环性能则会相应增强。若I×P×D×k的乘积B低于0.2,各参数数值较小,可能会因正极活性材料中锂过渡金属磷酸盐占比增大、正极活性材料压实密度降低、正极活性材料粒径减小及锂过渡金属氧化物为单晶结构而提高电化学装置的循环性能,但会导致能量密度受限。相对地,当B值超过5.7,各参数数值较大,可能会因锂过渡金属氧化物占比增大、压实密度增加、粒径增加易压实及锂过渡金属氧化物为多晶结构而提高电化学装置的能量密度,但会导致电化学装置的循环性能明显降低。因此,I×P×D×k在0.2至5.7时,四个参数适当取值,使得电化学装置可以兼顾高的能量密度和优异的循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This application relates to an electrochemical device and a positive electrode active material. The electrochemical device includes a positive electrode sheet, which includes a positive electrode current collector and a positive electrode film layer disposed on the surface of the positive electrode current collector and including a positive electrode active material. The positive electrode active material includes lithium transition metal oxide and lithium transition metal phosphate. The doping factor B of the positive electrode active material satisfies: 0.2≤B≤5.7, B=I×P×D×k, where I=a×b÷c, a is the molar percentage of nickel element based on the total molar amount of transition metal elements in the lithium transition metal oxide, b is the ratio of the mass percentage of lithium transition metal oxide in the positive electrode active material to the relative molecular mass of lithium transition metal oxide, c is the ratio of the mass percentage of lithium transition metal phosphate in the positive electrode active material to the relative molecular mass of lithium transition metal phosphate; P is the powder compaction density of the positive electrode active material under 3t pressure; D is the volume distribution particle size Dv50 of the positive electrode active material; when the lithium transition metal oxide is a polycrystalline material, k=2; when the lithium transition metal oxide is a single crystal material, k=1. This electrochemical device can balance energy density and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical technology, specifically relating to an electrochemical device and a positive electrode active material. Background Technology

[0002] The electric vehicle industry is developing rapidly, leading to a significant increase in demand for electrochemical devices. As a key material in electrochemical devices, positive electrode active materials play a crucial role in their electrical performance. With electric vehicles moving towards longer ranges and higher safety, improving energy density, extending lifespan, and enhancing material safety and stability are pressing issues for positive electrode active materials. Among these, lithium iron phosphate (LFP) materials have gained increasing attention due to their high safety, stability, and low cost.

[0003] For lithium iron phosphate (LFP) materials, their theoretical capacity and densest packing compaction have reached their limits, making it difficult to increase the energy density of electrochemical devices. To meet the higher energy density requirements of electrochemical devices, LFP materials can be blended with ternary cathode active materials that have higher capacity. However, with the addition of ternary cathode active materials, a small amount of ternary material will result in incomplete capacity utilization, while a large amount will lead to accelerated cycle life degradation of the electrochemical device. Therefore, how to balance the energy density and cycle performance of electrochemical devices in a hybrid system of LFP and ternary cathode active materials has become an urgent technical problem to be solved. Summary of the Invention

[0004] In view of this, the main objective of the present invention is to provide an electrochemical device and a positive electrode active material. This electrochemical device can balance energy density and cycle performance.

[0005] To achieve the above objectives, the technical solution of the present invention is implemented as follows:

[0006] A first aspect of the present invention provides an electrochemical device comprising an electrolyte, a positive electrode, and a negative electrode. The positive electrode comprises a positive current collector and a positive electrode film disposed on at least one surface of the positive current collector. The positive electrode film comprises a positive electrode active material, which comprises lithium transition metal oxide and lithium transition metal phosphate. The doping factor B of the positive electrode active material satisfies: 0.2 ≤ B ≤ 5.7, B = I × P × D × k, where I = a × b ÷ c, and a is the total amount of transition metal elements in the lithium transition metal oxide. In molar terms, b is the ratio of the mass percentage of nickel in the positive electrode active material to the relative molecular mass of lithium transition metal oxide; c is the ratio of the mass percentage of lithium transition metal phosphate in the positive electrode active material to the relative molecular mass of lithium transition metal phosphate; P is the powder compaction density of the positive electrode active material under 3t pressure; D is the volume distribution particle size Dv50 of the positive electrode active material; when the lithium transition metal oxide is a polycrystalline material, k = 2; when the lithium transition metal oxide is a single crystal material, k = 1.

[0007] In some implementations, I satisfies: 0.077≤I≤0.971.

[0008] In some embodiments, the powder compaction density P of the positive electrode active material under a pressure of 3t is 2.60 g / cm³. 3 Up to 2.90 g / cm 3 .

[0009] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material is from 1.12 μm to 2.80 μm.

[0010] In some embodiments, the molar percentage 'a' of nickel is 60% to 90% based on the total molar amount of transition metal elements in the lithium transition metal oxide.

[0011] In some embodiments, the ratio b of the mass percentage of lithium transition metal oxide in the positive electrode active material to the relative molecular mass of lithium transition metal oxide is 0.0005 to 0.0041.

[0012] In some embodiments, the ratio c of the mass percentage of lithium transition metal phosphate in the positive electrode active material to the relative molecular mass of lithium transition metal phosphate is 0.0038 to 0.0061.

[0013] In some embodiments, the mass ratio of lithium transition metal oxide to lithium transition metal phosphate is from 5:95 to 40:60.

[0014] In some embodiments, the lithium transition metal oxide satisfies one or more of the following characteristics:

[0015] (1) The compacted density of lithium transition metal oxide powder under a pressure of 3t is 3.0 g / cm³. 3 Up to 3.5g / cm 3 ;

[0016] (2) The discharge capacity of lithium transition metal oxide at 0.1C is 170 mAh / g to 220 mAh / g;

[0017] (3) The volume distribution particle size Dv50 of lithium transition metal oxides ranges from 3.4 μm to 10 μm.

[0018] A second aspect of the present invention provides a positive electrode active material comprising lithium transition metal oxide and lithium transition metal phosphate, wherein the doping factor B of the positive electrode active material satisfies: 0.2≤B≤5.7, B=I×P×D×k, where I=a×b÷c, a is the molar percentage of nickel element based on the total molar amount of transition metal elements in the lithium transition metal oxide, b is the ratio of the mass percentage of lithium transition metal oxide in the positive electrode active material to the relative molecular mass of lithium transition metal oxide, c is the ratio of the mass percentage of lithium transition metal phosphate in the positive electrode active material to the relative molecular mass of lithium transition metal phosphate; P is the powder compaction density of the positive electrode active material under 3t pressure; D is the volume distribution particle size Dv50 of the positive electrode active material; when the lithium transition metal oxide is a polycrystalline material, k=2; when the lithium transition metal oxide is a single crystal material, k=1.

[0019] In some implementations, I satisfies: 0.077≤I≤0.971.

[0020] In some embodiments, the powder compaction density P of the positive electrode active material under a pressure of 3t is 2.60 g / cm³. 3 Up to 2.90 g / cm 3 .

[0021] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material is from 1.12 μm to 2.80 μm.

[0022] In this application, the numerical range of I×P×D×k is limited to between 0.2 and 5.7 to ensure that the electrochemical device simultaneously possesses high energy density and excellent cycle performance. Specifically, parameter I represents the proportion of lithium transition metal oxide in the cathode active material, parameter P represents the compaction density of the cathode active material, parameter D represents the volume average particle size Dv50 of the cathode active material, and parameter k represents the crystal type of the lithium transition metal oxide (distinguishing between single crystal and polycrystalline). The values ​​of these four parameters are negatively correlated with the performance of the electrochemical device: the higher the parameter value, the higher the energy density of the electrochemical device, while the lower the parameter value, the better the cycle performance of the electrochemical device. If the product B of I×P×D×k is less than 0.2, the smaller the values ​​of each parameter, the higher the cycle performance of the electrochemical device may be due to the increased proportion of lithium transition metal phosphate in the cathode active material, the decreased compaction density of the cathode active material, the smaller particle size of the cathode active material, and the single crystal structure of the lithium transition metal oxide, but this will limit the energy density. Conversely, when the B value exceeds 5.7, the larger values ​​of each parameter may increase the energy density of the electrochemical device due to the increased proportion of lithium transition metal oxides, increased compaction density, easier compaction of larger particle size, and the polycrystalline structure of lithium transition metal oxides. However, this will lead to a significant decrease in the cycle performance of the electrochemical device. Therefore, when I×P×D×k is between 0.2 and 5.7, appropriate values ​​for the four parameters allow the electrochemical device to achieve both high energy density and excellent cycle performance. Detailed Implementation

[0023] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0024] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0025] Unless otherwise specified, the term "or" is inclusive in this invention. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0026] Unless otherwise specified, in this invention, "one or more" or "at least one" refers to any one, any two, or any two or more of the listed items. "Several" refers to any two or more.

[0027] The first aspect of this application provides an electrochemical device. This electrochemical device can be a lithium-ion battery, a sodium-ion battery, a lithium metal battery, or a sodium metal battery; however, the embodiments of this application are not limited to this type.

[0028] Typically, an electrochemical device includes a positive electrode, a negative electrode, a separator, and an electrolyte. During the charging and discharging process of the electrochemical device, active ions repeatedly insert and extract between the positive and negative electrodes. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits between them while allowing ions to pass through.

[0029] The electrochemical device of this application includes an electrolyte, a positive electrode, and a negative electrode. The positive electrode includes a positive current collector and a positive electrode film disposed on at least one surface of the positive current collector. The positive electrode film includes a positive electrode active material, which includes lithium transition metal oxide and lithium transition metal phosphate. The doping factor B of the positive electrode active material satisfies: 0.2 ≤ B ≤ 5.7, B = I × P × D × k, where I = a × b ÷ c, a is the total molar amount of transition metal elements in the lithium transition metal oxide, and nickel element... The molar percentage of lithium transition metal oxide in the positive electrode active material is given by: b is the ratio of the mass percentage of lithium transition metal oxide in the positive electrode active material to the relative molecular mass of lithium transition metal oxide; c is the ratio of the mass percentage of lithium transition metal phosphate in the positive electrode active material to the relative molecular mass of lithium transition metal phosphate; P is the powder compaction density of the positive electrode active material under a pressure of 3t; D is the volume distribution particle size Dv50 of the positive electrode active material; when the lithium transition metal oxide is a polycrystalline material, k = 2; when the lithium transition metal oxide is a single crystal material, k = 1.

[0030] In this application, parameter I reflects the proportion of lithium transition metal oxide in the mixed cathode active material system. When the value of I is small, the proportion of lithium transition metal oxide is small, resulting in a high shunting rate of lithium transition metal oxide. This high discharge rate will lead to the incomplete utilization of the capacity of lithium transition metal oxide, thus the improvement of the energy density of the electrochemical device is not significant. When the value of I is large, the proportion of lithium transition metal oxide is large, which will lead to the accelerated decay of the cycle life of the mixed system, thereby affecting the cycle performance of the electrochemical device.

[0031] The parameter P represents the compaction density of the positive electrode active material. When the P value is large, it is beneficial to increase the compaction density of the positive electrode sheet, thereby improving the energy density of the electrochemical device; when the P value is small, it is beneficial to improve the cycle performance of the electrochemical device.

[0032] The parameter D represents the volume distribution particle size Dv50 of the positive electrode active material. When the D value is large, it reflects that the particles of the positive electrode active material are larger. Larger particles are easier to achieve higher compaction density during the compaction process, thus resulting in higher energy density of the electrochemical device. When the D value is small, it reflects that the particles of the positive electrode active material are smaller. Smaller particles may better adapt to volume changes during cycling, reducing stress accumulation and crack formation caused by cycling, thereby improving the cycling performance of the electrochemical device.

[0033] The parameter k represents the crystal type of lithium transition metal oxide: when k = 2, lithium transition metal oxide is a polycrystalline material, which has better kinetic performance and is beneficial to improving the energy density of electrochemical devices; when k = 1, lithium transition metal oxide is a single crystal material, which has better structural stability and is beneficial to improving the cycle performance of electrochemical devices.

[0034] The values ​​of parameters I, P, D, and k exhibit a negative correlation with the performance of electrochemical devices: higher parameter values ​​lead to increased energy density, while lower values ​​result in improved cycle performance. If the product B of I × P × D × k is below 0.2, the smaller the parameter values, the higher the cycle performance may be due to an increased proportion of lithium transition metal phosphate in the cathode active material, decreased compaction density of the cathode active material, smaller particle size of the cathode active material, and the single-crystal structure of the lithium transition metal oxide, but this will limit energy density. Conversely, when B exceeds 5.7, the larger parameter values ​​may lead to increased energy density due to an increased proportion of lithium transition metal oxide, increased compaction density, easier compaction with larger particle size, and the polycrystalline structure of the lithium transition metal oxide, but this will significantly reduce the cycle performance of the electrochemical device.

[0035] Therefore, by ensuring that the product B of I, P, D, and k satisfies 0.2≤B≤5.7, the four parameters can be appropriately selected so that the electrochemical device can balance high energy density and excellent cycle performance.

[0036] For example, the doping factor B of the positive electrode active material is any value within the range of 0.2, 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 5.7 or any combination thereof.

[0037] In some implementations, I satisfies the condition: 0.077 ≤ I ≤ 0.971. A value within this range is beneficial for leveraging the high capacity of lithium transition metal oxides without affecting the cycle life of the mixed cathode active material system, thereby enabling the electrochemical device to achieve both high energy density and excellent cycle performance. For example, the value of I is any value within the range of 0.077, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.971, or any combination thereof.

[0038] In some embodiments, the powder compaction density P of the positive electrode active material under a pressure of 3t is 2.60 g / cm³. 3 Up to 2.90 g / cm 3 The compaction density of the positive electrode active material powder is within the aforementioned range, resulting in a more compact overall packing of the positive electrode active material. This increases the compaction density of the positive electrode sheet, which is beneficial for maintaining the high cycle performance of the electrochemical device while simultaneously improving its energy density. For example, the compaction density P of the positive electrode active material at a pressure of 3t is 2.60 g / cm³. 3 2.65g / cm 3 2.70 g / cm 3 2.75g / cm 3 2.80g / cm 3 2.85g / cm 3 2.90g / cm 3 Or any value within a range consisting of any two of them.

[0039] In some embodiments, the volumetric particle size distribution (Dv50) of the positive electrode active material is from 1.12 μm to 2.80 μm. A Dv50 within this range indicates that the particle size of the positive electrode active material is moderate. This is beneficial for the close packing of the positive electrode active material, thereby increasing the compaction density of the positive electrode sheet. Furthermore, it allows the positive electrode active material to better adapt to volume changes during cycling, reducing stress accumulation and crack formation caused by cycling. This, in turn, helps the electrochemical device achieve both high energy density and good cycling performance. Exemplarily, the Dv50 of the positive electrode active material is any value within the range of 1.12 μm, 1.20 μm, 1.40 μm, 1.60 μm, 1.80 μm, 2.00 μm, 2.20 μm, 2.40 μm, 2.60 μm, 2.80 μm, or any combination thereof.

[0040] In some embodiments, the molar percentage 'a' of nickel in the lithium transition metal oxide is 60% to 90% based on the total molar amount of transition metal elements in the lithium transition metal oxide. A molar percentage 'a' of nickel within this range is beneficial for increasing the capacity of the lithium transition metal oxide, thereby increasing the energy density of the electrochemical device. Exemplarily, the molar percentage 'a' of nickel in the lithium transition metal oxide is any value within the range of 60%, 65%, 70%, 75%, 80%, 85%, 90%, or any combination thereof, based on the total molar amount of transition metal elements in the lithium transition metal oxide.

[0041] In some embodiments, the ratio b of the mass percentage of lithium transition metal oxide in the cathode active material to the relative molecular mass of the lithium transition metal oxide is between 0.0005 and 0.0041. Parameter b reflects the proportion of lithium transition metal oxide in the cathode active material mixture. Since lithium transition metal oxide has a high capacity, when parameter b is within the above range, it is beneficial to improve the overall cycle life of the cathode active material while leveraging the high capacity of the lithium transition metal oxide, thereby enabling the electrochemical device to achieve both high energy density and excellent cycle performance. For example, the ratio b of the mass percentage of lithium transition metal oxide in the cathode active material to the relative molecular mass of the lithium transition metal oxide is any value within the range of 0.0005, 0.0010, 0.0015, 0.0020, 0.0025, 0.0030, 0.0035, 0.0040, 0.0041, or any combination thereof.

[0042] In some embodiments, the ratio c of the mass percentage of lithium transition metal phosphate in the cathode active material to the relative molecular mass of lithium transition metal phosphate is between 0.0038 and 0.0061. Parameter c reflects the proportion of lithium transition metal phosphate in the cathode active material mixture. Since lithium transition metal phosphate has high structural stability, when parameter c is within the above range, it is beneficial to improve the overall cycle life of the cathode active material while leveraging the high capacity of lithium transition metal oxides, thereby enabling the electrochemical device to achieve both high energy density and excellent cycle performance. For example, the ratio c of the mass percentage of lithium transition metal phosphate in the cathode active material to the relative molecular mass of lithium transition metal phosphate is any value within the range of 0.0038, 0.0040, 0.0045, 0.0050, 0.0055, 0.0060, 0.0061, or any combination thereof.

[0043] The following is a further explanation of the components of the electrochemical device:

[0044] Positive electrode sheet

[0045] In this application, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side surface of the positive current collector. The positive electrode film layer includes a positive electrode active material, which includes lithium transition metal oxide and lithium transition metal phosphate.

[0046] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0047] In some embodiments, the mass ratio of lithium transition metal oxide to lithium transition metal phosphate is from 5:95 to 40:60. A mass ratio of lithium transition metal oxide to lithium transition metal phosphate within this range is advantageous for improving the overall cycle life of the cathode active material while leveraging the high capacity of the lithium transition metal oxide, thereby enabling the electrochemical device to achieve both high energy density and excellent cycle performance. Exemplarily, the mass ratio of lithium transition metal oxide to lithium transition metal phosphate is any value within the range of 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60, or any combination thereof.

[0048] In some embodiments, the compaction density of the lithium transition metal oxide powder at a pressure of 3t is 3.0 g / cm³. 3 Up to 3.5g / cm 3The compaction density of lithium transition metal oxide powder within the aforementioned range is beneficial for improving the packing density of lithium transition metal oxide, thereby increasing the compaction density of the positive electrode and enhancing the energy density of the electrochemical device. For example, the compaction density of lithium transition metal oxide powder at a pressure of 3t is 3.0 g / cm³. 3 3.1g / cm 3 3.2g / cm 3 3.3g / cm 3 3.4g / cm 3 3.5g / cm 3 Or any value within a range consisting of any two of them.

[0049] In this application, the powder compaction density of the positive electrode active material and the lithium transition metal oxide can be determined using instruments and methods known in the art, such as a powder compaction density meter. Specifically, 1g of positive electrode active material powder and 1g of lithium transition metal oxide powder are weighed and added to a mold, pressurized to 30KN, with a pressurization displacement of 10mm / min and a pressurization holding time of 30s. Then, the pressure is released, with a release displacement of 30mm / min and a release holding time of 10s. The powder compaction density of the positive electrode active material and the lithium transition metal oxide under a pressure of 3t is recorded and calculated.

[0050] In some embodiments, the discharge capacity of the lithium transition metal oxide at 0.1C is between 170 mAh / g and 220 mAh / g. The discharge capacity of the lithium transition metal oxide at 0.1C falling within this range reflects that the lithium transition metal oxide has a high capacity, and the electrochemical device employing the aforementioned lithium transition metal oxide can have a high energy density. Exemplarily, the discharge capacity of the lithium transition metal oxide at 0.1C is any value within the range of 170 mAh / g, 180 mAh / g, 190 mAh / g, 200 mAh / g, 210 mAh / g, 220 mAh / g, or any combination thereof.

[0051] In this application, the discharge capacity of lithium transition metal oxide at 0.1C can be determined by the following method: Lithium transition metal oxide, binder, and conductive agent are mixed and added to the solvent N-methylpyrrolidone, stirred evenly to form a positive electrode slurry. The positive electrode slurry is coated onto a positive electrode current collector, dried, and cold-pressed to obtain a positive electrode test sheet. The positive electrode test sheet is assembled with a lithium sheet into a coin cell. The coin cell is then charged at a constant current of 0.1C to 4.25V, then charged at a constant voltage of 4.25V to a current of 0.05C. After standing for 30 minutes, it is discharged at a constant current of 0.1C to 2.0V to obtain the discharge capacity of lithium transition metal oxide at 0.1C.

[0052] In some embodiments, the volumetric particle size distribution (Dv50) of the lithium transition metal oxide is between 3.4 μm and 10 μm. A volumetric particle size distribution (Dv50) within this range is beneficial for the lithium transition metal oxide and lithium transition metal phosphate to form a particle size distribution, thereby increasing the overall powder compaction density of the cathode active material and improving the energy density of the electrochemical device. Furthermore, it can improve the rate performance of the lithium transition metal oxide, which is beneficial for the overall capacity utilization of the cathode active material. For example, the volumetric particle size distribution (Dv50) of the lithium transition metal oxide is any value within the range of 3.4 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any combination thereof.

[0053] In this application, the term "Dv50" refers to the particle size corresponding to a cumulative volume distribution percentage of 50% for the material. The volume distribution particle size Dv50 of the positive electrode active material and lithium transition metal oxide can be determined using instruments and methods known in the art, for example, it can be determined using a laser particle size analyzer with reference to standard GB / T 19077-2016. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0054] In some embodiments, the lithium transition metal oxide includes lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, and lithium nickel cobalt manganese oxide (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 ), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05One or more of O2 and its modified compounds; optionally, lithium transition metal oxides include lithium nickel cobalt manganese oxides. Thus, lithium nickel cobalt manganese oxides exhibit higher capacity, resulting in improved energy density in electrochemical devices.

[0055] In some embodiments, the lithium transition metal phosphate includes one or more of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites; optionally, the lithium transition metal phosphate includes lithium iron phosphate. Therefore, lithium iron phosphate exhibits high structural stability, resulting in excellent safety performance of the electrochemical device.

[0056] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0057] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0058] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0059] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0060] electrolytes

[0061] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.

[0062] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0063] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0064] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0065] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain performance of the electrochemical device, such as additives that improve the overcharge performance of the electrochemical device, additives that improve the high-temperature or low-temperature performance of the electrochemical device, etc.

[0066] Negative electrode sheet

[0067] In this application, the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0068] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0069] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0070] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. Silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0071] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0072] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0073] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0074] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0075] Separating membrane

[0076] In this application, the electrochemical device also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0077] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0078] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0079] A second aspect of the present invention provides a positive electrode active material comprising lithium transition metal oxide and lithium transition metal phosphate. The doping factor B of the positive electrode active material satisfies: 0.2 ≤ B ≤ 5.7, B = I × P × D × k, where I = a × b ÷ c, a is the molar percentage of nickel based on the total molar amount of transition metal elements in the lithium transition metal oxide, b is the ratio of the mass percentage of lithium transition metal oxide in the positive electrode active material to the relative molecular mass of lithium transition metal oxide, c is the ratio of the mass percentage of lithium transition metal phosphate in the positive electrode active material to the relative molecular mass of lithium transition metal phosphate; P is the powder compaction density of the positive electrode active material under 3t pressure; D is the volume distribution particle size Dv50 of the positive electrode active material; when the lithium transition metal oxide is a polycrystalline material, k = 2; when the lithium transition metal oxide is a single crystal material, k = 1.

[0080] In some implementations, I satisfies: 0.077≤I≤0.971.

[0081] In some embodiments, the powder compaction density P of the positive electrode active material under a pressure of 3t is 2.60 g / cm³. 3 Up to 2.90 g / cm 3 .

[0082] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material is from 1.12 μm to 2.80 μm.

[0083] Example 1

[0084] The preparation method of the electrochemical device is as follows:

[0085] (1) Preparation of positive electrode sheet

[0086] Single-crystal lithium transition metal oxide (LiNi) 0.6 Co 0.1 Mn 0.3 O2), lithium transition metal phosphate (lithium iron phosphate), conductive carbon black (SP), and polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 18.4:73.6:5:3 in the solvent N-methylpyrrolidone and stirred until homogeneous to obtain the positive electrode slurry. Among them, LiNi 0.6 Co 0.1 Mn 0.3O2 and lithium iron phosphate are used together as positive electrode active materials. Based on the total molar amount of transition metal elements in lithium transition metal oxide, the molar proportion of nickel (a) is 60%, the ratio of the mass proportion of lithium transition metal oxide in the positive electrode active material to the relative molecular mass of lithium transition metal oxide (b) is 0.00207, the ratio of the mass proportion of lithium transition metal phosphate in the positive electrode active material to the relative molecular mass of lithium transition metal phosphate (c) is 0.00507, I = a × b ÷ c = 0.245, k = 1;

[0087] Aluminum foil was used as the positive electrode current collector. The positive electrode slurry was coated on both sides of the positive electrode current collector and baked at 85°C for 1 hour. Then, it was cold pressed, cut, and slit to prepare the positive electrode sheet, wherein the thickness of the positive electrode film layer was 100 μm.

[0088] The parameters of the obtained positive electrode were tested using the following method:

[0089] Powder compaction density test:

[0090] The lithium transition metal oxide LiNi in Example 1 was tested using a SUNS powder compaction density meter. 0.6 Co 0.1 Mn 0.3 The compaction density of O2, lithium iron phosphate (LiFePO4), and positive electrode active material powders was determined: 1g of lithium transition metal oxide powder (LiNi) was weighed out. 0.6 Co 0.1 Mn 0.3 O2, 1g of lithium iron phosphate powder, and 1g of positive electrode active material powder were added to a mold, pressurized to 3t with a pressure displacement of 10mm / min and a holding time of 30s. Then, the pressure was released with a release displacement of 30mm / min and a holding time of 10s. The values ​​of lithium transition metal oxide (LiNi) were recorded and calculated. 0.6 Co 0.1 Mn 0.3 Powder compaction density of O2, lithium iron phosphate and positive electrode active material under 3t pressure.

[0091] LiNi, a lithium transition metal oxide, in Example 1 0.6 Co 0.1 Mn 0.3 The compacted density of O2 powder under a pressure of 3t is 3.4 g / cm³. 3 The compacted density of lithium iron phosphate powder under 3t pressure is 2.55 g / cm³. 3 The compacted density of the positive electrode active material powder under a pressure of 3t is 2.74 g / cm³. 3 .

[0092] Volume distribution particle size test:

[0093] A Malvern 3000 (MasterSizer 3000) laser particle size analyzer was used, following the standard procedure GB / T19077-2016 / ISO 13320:2009, to analyze lithium transition metal oxide (LiNi). 0.6 Co 0.1 Mn 0.3 The volume distribution and particle size of O2, lithium iron phosphate (LiFePO4), and positive electrode active material were tested.

[0094] LiNi, a lithium transition metal oxide, in Example 1 0.6 Co 0.1 Mn 0.3 The volume distribution particle size Dv50 of O2 is 3.8 μm, that of lithium iron phosphate is 0.98 μm, and that of the positive electrode active material is 1.56 μm.

[0095] Discharge capacity test:

[0096] The lithium transition metal oxide LiNi from Example 1 0.6 Co 0.1 Mn 0.3 O2 is mixed with binder and conductive agent and then added to solvent N-methylpyrrolidone. The mixture is stirred until homogeneous to form a positive electrode slurry. The positive electrode slurry is coated onto the positive electrode current collector, dried, and cold-pressed to obtain the positive electrode test sheet. The positive electrode test sheet is assembled with a lithium sheet into a coin cell. The coin cell is then charged at a constant current of 0.1C to 4.25V, then charged at a constant voltage of 4.25V to a current of 0.05C. After standing for 30 minutes, it is discharged at a constant current of 0.1C to 2.0V to obtain the discharge capacity of lithium transition metal oxide at 0.1C.

[0097] The lithium iron phosphate (LiFePO4) from Example 1 was mixed with a binder and a conductive agent, then added to the solvent N-methylpyrrolidone and stirred until homogeneous to form a positive electrode slurry. This slurry was coated onto a positive electrode current collector, dried, and cold-pressed to obtain a positive electrode test sheet. The positive electrode test sheet and a lithium sheet were assembled into a coin cell. The coin cell was then charged at a constant current of 0.1C to 4.25V, then charged at a constant voltage of 4.25V to a current of 0.05C. After standing for 30 minutes, it was discharged at a constant current of 0.1C to 2.0V, yielding the discharge capacity of the lithium transition metal phosphate at 0.1C.

[0098] LiNi, a lithium transition metal oxide, in Example 1 0.6 Co 0.1 Mn 0.3The discharge capacity of O2 at 0.1C is 170mAh / g, and the discharge capacity of lithium iron phosphate at 0.1C is 159mAh / g.

[0099] (2) Preparation of electrolytes

[0100] In an argon atmosphere, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:1:1 to form a solvent. Lithium hexafluorophosphate (LiPF6) was then added to the solvent to obtain an electrolyte with a mass fraction of 12.5% ​​lithium hexafluorophosphate.

[0101] (3) Preparation of the separating membrane

[0102] A 24μm polypropylene film was used as the separator.

[0103] (4) Assembly of electrochemical devices

[0104] The above-mentioned positive electrode, lithium plate, separator and electrolyte are assembled into an electrochemical device (button cell) in an argon-protected glove box.

[0105] After the obtained electrochemical device was allowed to stand for 12 hours, its performance was tested using the following method:

[0106] First discharge specific capacity test:

[0107] At 25°C, the electrochemical device prepared in Example 1 was charged to 4.25V with a constant current of 0.1C, and then charged to 0.05C with a constant voltage of 4.25V, and left to stand for 30 minutes. Then it was discharged to 2.0V with a constant current of 0.1C. The discharge capacity D1 of the first cycle was recorded, and the ratio of D1 to the mass of the positive electrode active material was calculated to obtain the first discharge specific capacity. The test results are recorded in Table 1 below.

[0108] The initial discharge specific capacity reflects the energy density of an electrochemical device. A high initial discharge specific capacity indicates that the electrochemical device has excellent energy density.

[0109] High-temperature cycling performance test:

[0110] At 45°C, the electrochemical device prepared in Example 1 was charged to 4.25V with a constant current of 1C, allowed to stand for 5 minutes, and then discharged to 2.5V with a constant current of 1C, allowed to stand for 5 minutes. This was the first cycle, and the discharge capacity of the first cycle was recorded as C0. The above steps were repeated for 80 cycles, and the discharge capacity of the 80th cycle was recorded as Cn. The capacity retention rate of the 80th cycle was (Cn / C0)×100%. The test results are recorded in Table 1 below.

[0111] Among them, capacity retention rate can reflect the cycle performance of electrochemical devices. A high capacity retention rate indicates that the electrochemical device has excellent cycle performance.

[0112] Example 2

[0113] The electrochemical device was prepared using the same method as in Example 1, except that the type of lithium transition metal oxide was adjusted according to Table 1, and / or the mass ratio of lithium transition metal oxide to lithium transition metal phosphate was adjusted. In Example 2, the doping factor B of the positive electrode active material was 5.3.

[0114] Example 3

[0115] The electrochemical device was prepared using the same method as in Example 1, except that the type of lithium transition metal oxide was adjusted according to Table 1, and / or the mass ratio of lithium transition metal oxide to lithium transition metal phosphate was adjusted. In Example 3, the doping factor B of the positive electrode active material was 1.4.

[0116] Example 4

[0117] The electrochemical device was prepared using the same method as in Example 1, except that the type of lithium transition metal oxide was adjusted according to Table 1, and / or the mass ratio of lithium transition metal oxide to lithium transition metal phosphate was adjusted. In Example 4, the doping factor B of the positive electrode active material was 5.7.

[0118] Example 5

[0119] The electrochemical device was prepared using the same method as in Example 1, except that the type of lithium transition metal oxide was adjusted according to Table 1, and / or the mass ratio of lithium transition metal oxide to lithium transition metal phosphate was adjusted. In Example 5, the doping factor B of the positive electrode active material was 0.2.

[0120] Example 6

[0121] The electrochemical device was prepared using the same method as in Example 1, except that the type of lithium transition metal oxide was adjusted according to Table 1, and / or the mass ratio of lithium transition metal oxide to lithium transition metal phosphate was adjusted. In Example 6, the doping factor B of the positive electrode active material was 0.5.

[0122] Example 7

[0123] The electrochemical device was prepared using the same method as in Example 1, except that the type of lithium transition metal oxide was adjusted according to Table 1, and / or the mass ratio of lithium transition metal oxide to lithium transition metal phosphate was adjusted. In Example 7, the doping factor B of the positive electrode active material was 1.5.

[0124] Example 8

[0125] The electrochemical device was prepared using the same method as in Example 1, except that the type of lithium transition metal oxide was adjusted according to Table 1, and / or the mass ratio of lithium transition metal oxide to lithium transition metal phosphate was adjusted. In Example 8, the doping factor B of the positive electrode active material was 3.1.

[0126] Example 9

[0127] The electrochemical device was prepared using the same method as in Example 1, except that the type of lithium transition metal oxide was adjusted according to Table 1, and / or the mass ratio of lithium transition metal oxide to lithium transition metal phosphate was adjusted. In Example 9, the doping factor B of the positive electrode active material was 5.5.

[0128] Comparative Example 1

[0129] The electrochemical device was prepared using the same method as in Example 1, except that the type of lithium transition metal oxide was adjusted according to Table 1, and / or the mass ratio of lithium transition metal oxide to lithium transition metal phosphate was adjusted. In Comparative Example 1, the doping factor B of the positive electrode active material was 0.04.

[0130] Comparative Example 2

[0131] The electrochemical device was prepared using the same method as in Example 1, except that the type of lithium transition metal oxide was adjusted according to Table 1, and / or the mass ratio of lithium transition metal oxide to lithium transition metal phosphate was adjusted. In Comparative Example 2, the doping factor B of the positive electrode active material was 9.9.

[0132] The lithium transition metal oxides of Examples 2 to 9 and Comparative Examples 1 and 2 were subjected to parameter testing using the same test methods as in Example 1, and the test results are shown in Table 1 below. The positive electrode active materials obtained in Examples 2 to 9 and Comparative Examples 1 and 2 were subjected to parameter testing using the same test methods as in Example 1, and the electrochemical devices were subjected to performance testing, and the test results are shown in Table 2 below.

[0133] Table 1

[0134]

[0135] Table 2

[0136]

[0137]

[0138] In Table 2, a represents the molar percentage of nickel based on the total molar amount of transition metal elements in lithium transition metal oxides; b represents the ratio of the mass percentage of lithium transition metal oxides in the positive electrode active material to the relative molecular mass of lithium transition metal oxides; c represents the ratio of the mass percentage of lithium transition metal phosphates in the positive electrode active material to the relative molecular mass of lithium transition metal phosphates; I = a × b ÷ c; D represents the volume distribution particle size Dv50 of the positive electrode active material; P represents the powder compaction density of the positive electrode active material under a pressure of 3t; when the lithium transition metal oxide is a polycrystalline material, k = 2, and when the lithium transition metal oxide is a single crystal material, k = 1; B represents the doping factor of the positive electrode active material, B = I × P × D × k.

[0139] As can be seen from the data in Tables 1 and 2, compared with Comparative Example 1 (B less than 1.2) and Comparative Example 2 (B greater than 5.7), Examples 1 to 9 can meet the following condition by controlling the doping factor B of the positive electrode active material: 0.2≤B≤5.7, so that the electrochemical device can achieve both high energy density and excellent cycle performance.

[0140] Among them, the mixing factor B of the positive electrode active material is related to the I value, the powder compaction density P of the positive electrode active material under 3t pressure, the volume distribution particle size Dv50 (denoted as D) of the positive electrode active material, and the crystal form of the lithium transition metal oxide. The I value is related to the molar proportion of nickel (a) based on the total molar amount of transition metal elements in the lithium transition metal oxide, the ratio of the mass proportion of lithium transition metal oxide in the positive electrode active material to the relative molecular mass of lithium transition metal oxide (b), and the ratio of the mass proportion of lithium transition metal phosphate in the positive electrode active material to the relative molecular mass of lithium transition metal phosphate (c). By controlling a to 60% to 90%, b to 0.0005 to 0.0041, and c to 0.0038 to 0.0061, the I value can satisfy 0.077 ≤ I ≤ 0.971. When the I value is 0.077 to 0.971, the P value is 2.60 g / cm³. 3 Up to 2.90 g / cm 3 When the D value is between 1.12 μm and 2.80 μm, by coordinating and controlling the four parameters I, P, D and k, the doping factor B of the positive electrode active material can be made to satisfy: 0.2≤B≤5.7, thereby enabling the electrochemical device to achieve both high energy density and excellent cycle performance.

[0141] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. An electrochemical device, characterized in that, The electrochemical device includes an electrolyte, a positive electrode, and a negative electrode. The positive electrode includes a positive current collector and a positive electrode film disposed on at least one surface of the positive current collector. The positive electrode film includes a positive electrode active material, which includes lithium transition metal oxide and lithium transition metal phosphate. The doping factor B of the positive electrode active material satisfies: 0.2 ≤ B ≤ 5.7, B = I × P × D × k. Where I = a × b ÷ c, a is the molar percentage of nickel based on the total molar amount of transition metal elements in the lithium transition metal oxide, b is the ratio of the mass percentage of the lithium transition metal oxide in the positive electrode active material to the relative molecular mass of the lithium transition metal oxide, and c is the ratio of the mass percentage of the lithium transition metal phosphate in the positive electrode active material to the relative molecular mass of the lithium transition metal phosphate. P is the compaction density of the positive electrode active material under a pressure of 3t; D is the volume distribution particle size Dv50 of the positive electrode active material; When the lithium transition metal oxide is a polycrystalline material, k = 2; when the lithium transition metal oxide is a single-crystal material, k = 1.

2. The electrochemical device according to claim 1, characterized in that, The condition I satisfies: 0.077≤I≤0.

971.

3. The electrochemical device according to claim 1 or 2, characterized in that, The compacted density P of the positive electrode active material under a pressure of 3t is 2.60 g / cm³. 3 Up to 2.90 g / cm 3 .

4. The electrochemical device according to any one of claims 1 to 3, characterized in that, The volume distribution particle size Dv50 of the positive electrode active material is from 1.12 μm to 2.80 μm.

5. The electrochemical device according to any one of claims 1 to 4, characterized in that, Based on the total molar amount of transition metal elements in the lithium transition metal oxide, the molar percentage of nickel, a, is 60% to 90%.

6. The electrochemical device according to any one of claims 1 to 5, characterized in that, The ratio b of the mass percentage of the lithium transition metal oxide in the positive electrode active material to the relative molecular mass of the lithium transition metal oxide is 0.0005 to 0.0041.

7. The electrochemical device according to any one of claims 1 to 6, characterized in that, The ratio c of the mass percentage of the lithium transition metal phosphate in the positive electrode active material to the relative molecular mass of the lithium transition metal phosphate is 0.0038 to 0.0061.

8. The electrochemical device according to any one of claims 1 to 7, characterized in that, The mass ratio of the lithium transition metal oxide to the lithium transition metal phosphate is from 5:95 to 40:

60.

9. The electrochemical device according to any one of claims 1 to 8, characterized in that, The lithium transition metal oxide satisfies one or more of the following characteristics: (1) The compacted density of the lithium transition metal oxide powder under a pressure of 3t is 3.0 g / cm³. 3 Up to 3.5g / cm 3 ; (2) The discharge capacity of the lithium transition metal oxide at 0.1C is 170 mAh / g to 220 mAh / g; (3) The volume distribution particle size Dv50 of the lithium transition metal oxide is 3.4 μm to 10 μm.

10. A positive electrode active material, characterized in that, The positive electrode active material includes lithium transition metal oxide and lithium transition metal phosphate. The doping factor B of the positive electrode active material satisfies: 0.2 ≤ B ≤ 5.7, B = I × P × D × k. Where I = a × b ÷ c, a is the molar percentage of nickel based on the total molar amount of transition metal elements in the lithium transition metal oxide, b is the ratio of the mass percentage of the lithium transition metal oxide in the positive electrode active material to the relative molecular mass of the lithium transition metal oxide, and c is the ratio of the mass percentage of the lithium transition metal phosphate in the positive electrode active material to the relative molecular mass of the lithium transition metal phosphate. P is the compaction density of the positive electrode active material under a pressure of 3t; D is the volume distribution particle size Dv50 of the positive electrode active material; When the lithium transition metal oxide is a polycrystalline material, k = 2; when the lithium transition metal oxide is a single-crystal material, k = 1.

11. The positive electrode active material according to claim 10, characterized in that, The condition I satisfies: 0.077≤I≤0.

971.

12. The positive electrode active material according to claim 10 or 11, characterized in that, The compacted density P of the positive electrode active material under a pressure of 3t is 2.60 g / cm³. 3 Up to 2.90 g / cm 3 .

13. The positive electrode active material according to any one of claims 10 to 12, characterized in that, The volume distribution particle size Dv50 of the positive electrode active material is from 1.12 μm to 2.80 μm.